Uji Efektifitas Gel Ekstrak Sambung Nyawa (Gynura Procumbens (Lour.)Merr.) Terhadap Penyembuhan Luka Pada Kelinci Hiperglikemia - Ganet Eko Pramukantoro; Sri Rejeki Handayani (Fakultas Farmasi Universitas Setia Budi, 2021)
Hyperglycemia can inhibit the wounds healing process. Giving life-sustained leaf extract gel (Gynura procumbens (Lour.) Merr.) Is one of the options. The long-term goal of this study is to prove that the gel extract (Gynura procumbens (Lour.) Merr.) Leaf extract gel is able to heal wounds in hyperglycemic test animals. The specific target to be achieved is to obtain efficacious natural medicines to prevent the occurrence of diabetic wounds and to know the effective dosage of gel extract extract (Gynura procumbens (Lour.) Merr.) As a cure for diabetic wounds. This study used 5 white rabbits. Testing is done by making a wound on the back of DM alloxan-induced test animals. Wound healing activity is seen by dividing the backs of test animals into 5 parts which are treated according to their groups. The treatment group and the positive control group were applied with gel twice a day for 9 days and measured the length of the wound on days 1, 3, 5, 7, and 9. Diabetic wound healing activity was shown by calculating the wound length of each treatment and analyzed with the Anova test one way with a 95% confidence level. The results of the study showed that the formulation of life grafting gel extract based on CMC Na had good physical quality test results such as organoleptic color test according to the color of the extract, distinctive aroma of the life span leaf extract, viscous, homogeneous appearance, had a pH of 6. For the dispersion test , adhesion, and viscosity, each meets the desired requirements. The wound healing activity test showed that the grafted leaf extract with a concentration of 5% was able to heal the best, with a percentage of wound healing of 67.00%.